Alpha lipoic acid combined with epalrestat: a therapeutic option for patients with diabetic peripheral neuropathy - Wang, Xiaotong (Drug Des Devel Ther, 2018)
BACKGROUND: Alpha lipoic acid (ALA), a type of antioxidant, is used in combination with epalrestat in the treatment of diabetic peripheral neuropathy (DPN). However, whether combined treatment is superior to epalrestat monotherapy is controversial. METHODS: We conducted a systematic search of PubMed, Cochrane Library and Chinese databases to identify all randomized controlled trials (RCTs) up to October 31, 2017. Data were extracted to evaluate methodological quality and analyzed using Review Manager 5.3.0 software. RESULTS: Twelve studies were included. Compared to epalrestat monotherapy, ALA 600 mg/d once a day (qd) combined with epalrestat 50 mg three times a day (tid) augmented the total effectiveness rate (14 days – risk ratio [RR]: 1.40, 95% CI: 1.16–1.69, P=0.0005; 28 days – RR: 1.48, 95% CI: 1.27–1.72, P<0.00001); at the same, it could improve the median motor nerve conduction velocity (MNCV) and sensory nerve conduction velocity (SNCV), peroneal MNCV, and SNCV after 14, 21, and 28 days of treatment and could reduce the Toronto Clinical Scoring System (TCSS) (weighted mean difference [WMD]: −1.60, 95% CI: (−2.91, −0.29), P=0.02) and Total Symptom Score (TSS) (WMD: −0.93, 95% CI: −1.27, −0.60, P<0.00001) after 21 days of treatment. The treatment strategy of ALA 300 mg/d qd combined with epalrestat 50 mg tid had the same effects in regard to the total effectiveness rate (RR: 1.37, 95% CI: 1.18–1.59, P<0.0001), median MNCV (WMD: 6.12, 95% CI: 5.04, 7.20, P=0.00001), median SNCV (WMD: 6.70, 95% CI: 5.75, 7.65, P=0.00001), peroneal MNCV (WMD: 6.68, 95% CI: 5.82, 7.55, P=0.00001), and peroneal SNCV (WMD: 4.27, 95% CI: 3.34, 5.20, P=0.00001) after 28 days of treatment. CONCLUSION: ALA combined with epalrestat is an effective option for DPN patients. Future large-sample RCTs should be conducted to further confirm this finding.